Сравнение методов стеганографии в изображениях - Мартовицкий, В. А.; Кортяк, Е. (ХНУРЕ, 2019)
Steganography is a method of hiding information in other information of different format (container). There are many steganography techniques with various types of container. In the Internet, digital images are the most popular and frequently used containers. We consider main image steganography techniques and their advantages and disadvantages. We also identify the requirements of a good steganography algorithm and compare various such algorithms
Keywords: стеганорграфия; искажение данных; скрытый канал связи